GAMBARAN MATERI DAN KATA KERJA OPERASIONAL (KKO) YANG TERDAPAT PADA TUJUAN PEMBELAJARAN (RRP) DI SMAN SEKOTA PAINAN - Susanti, Nova; Zafri, Zafri; Husnita, Liza (Pendidikan Sejarah, 2014)
This research is motivated by the teaching materials chosen by teachers, one of them at SMAN 1 Painan indicate that teaching materials are contained in the RPP generally contains about facts, concepts and principles, but not complete, as the RPP class x SMAN 1 Painan no principle. So it is not balanced it between the material taught in SMAN 2 and SMAN 3 Painan.Based on these problems, the method used in this research is descriptive quantitative method, which is to see and describe what it reveals anything, it is desirable from this study is deskiptif, description of materials and Verbs Oprasional (Marines) contained on learning objectives (RPP). To know the material and Operations Verbs (Marines) pembelajarn purposes only studied in the lesson plan.he results showed that the material contained on learning objectives, lesson plans teachers Painan in SMA 1, SMA Negeri 2 Painan and SMA Negeri 3 Painan. RPP SMAN 1 Painan teachers and teachers of SMAN 2 Painan more material about the concept of teacher lesson plans while SMA 3 Painan more about the facts. Verbs are There At RPP Learning Objectives 1 Painan State High School teacher, said operational work that is generally used to describe. Operational verb used means teachers want students to have the ability to understand the meaning, explaining, reiterating an idea urther analysis shows that the Operations Verbs (Marines) are used in SMAN 1 and SMAN 2 Painan Painan less relevant, while at SMAN 3 Painan been better. Based on the above findings it can be concluded that teachers of SMAN 1 and SMAN 2 Painan Painan lack of understanding about the type of material and Operations Verbs (Marines). While teachers of SMAN 3 Painan less meseimbangkan type of material. It is recommended that working with colleagues in the manufacture of the learning objectives.